The Determination of Availability Path Planning in Natural Tourist Attractions using Dijkstra's Algorithm and Ant Colony Optimization - Gustami, Heri; Rizal, Muhammad; Fajri, Riyadhul (Journal of Computer System and Informatics (JoSYC), 2024)
The research on determining Availability Path Planning for natural tourist attractions using Dijkstra and Ant Colony algorithms aims to identify the most efficient routes in terms of time, distance, and environmental conditions. This is achieved by combining the Dijkstra and Ant Colony Optimization algorithms, each with its respective advantages and disadvantages, to create a system for finding the shortest, fastest, and safest paths to natural tourist destinations in Bireuen Regency. The methodology employed in this study is the waterfall model, which encompasses stages from analysis to application development, integrating both Dijkstra and Ant Colony Optimization algorithms. The research findings reveal that the shortest route to the Ceuraceu Waterfall destination can be accessed via the Samagadeng Village road in Pandrah District, while the longest route can be accessed through the city center of Bireuen Regency. Furthermore, for the Krueng Simpo River Bathing Tourism, the shortest route is via the Gayo Bireuen road, while the longest route is through the KKA Aceh Utara road. Lastly, the shortest route to the Kuala Jangka Beach tourist attraction is via the Jangka road from the Matangglumpang Dua area, while the longest route can be accessed through the Kuala Bireuen road.